Analisis Manajemen Rantai Pasok pada UMKM Tahu Menggunakan Metode Economic Order Quantity (EOQ) - Sani, Rahma; Ramadhani, Indah; Harmutika, Della (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Tofu Micro, Small and Medium Enterprises (MSMEs) in Pandau Jaya Village are individual businesses operating in the food industry, especially tofu production. This research aims to analyze the supply chain performance of tofu MSMEs in Pandau Jaya Village and the impact of optimizing supply chain management on supply. This research method is descriptive qualitative using primary and secondary data. The research results show that the supply chain management of tofu products in Tofu MSMEs in Pandau Jaya Village is running well. All elements of the supply chain, including soybean agents, Tahu Pandau Jaya Village MSMEs, and consumers are running well. Supply chain management is considered effective, especially in transactions, policies and capital. Chain resources, such as people, technology and capital, operate optimally, supporting the smooth production of tofu. The chain business process is considered optimal, reflecting solid business relationships between supply chain members, based on good trust